2019
DOI: 10.1186/s12864-019-5758-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analyses of genes involved in sulforaphane metabolism at different treatment in Chinese kale using full-length transcriptome sequencing

Abstract: Background Sulforaphane is a natural isothiocyanate available from cruciferous vegetables with multiple characteristics including antioxidant, antitumor and anti-inflammatory effect. Single-molecule real-time (SMRT) sequencing has been used for long-read de novo assembly of plant genome. Here, we investigated the molecular mechanism related to glucosinolates biosynthesis in Chinese kale using combined NGS and SMRT sequencing. Results SMRT sequencing produced 185,134 uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…The use of high-throughput transcriptome technologies enables to investigate the genetic responses that organisms deploy in alternative environments (Roy et al, 2010). So far, RNA-seq was employed to evaluate the changes induced by different treatments (Zheng et al, 2013;Alfonso-Parra et al, 2016;Wu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The use of high-throughput transcriptome technologies enables to investigate the genetic responses that organisms deploy in alternative environments (Roy et al, 2010). So far, RNA-seq was employed to evaluate the changes induced by different treatments (Zheng et al, 2013;Alfonso-Parra et al, 2016;Wu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In general, terpenoids are regarded as phytoanticipins, which are involved in responding to biotic and abiotic stresses ( Dixon, 2001 ). Salicylic acid (SA) is an endogenous signal substance that exists universally in plants ( Wu et al, 2019 ). It exhibit that SA is perceived by the Non-expresser of PR (NPRs) receptors, and functions directly in the activation of defense responses ( Sawai and Saito, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…RNA-seq has been performed to identify the putative genes involved in terpenoid biosynthesis in multiple plants ( Luo et al, 2011 ; Ma et al, 2016 ; Wang et al, 2017 ; Zhou et al, 2017 ; Choudhri et al, 2018 ; Shan et al, 2020 ). Nevertheless, the short read lengths from RNA-seq restrict the construction of completely assembled transcripts, making it difficult to obtain full-length sequences ( Wu et al, 2019 , 2020 ). As a third-generation sequencing technique, single-molecule real-time (SMRT) sequencing can generate full-length cDNA sequences without post-sequencing assembly, which basically overcomes the limitation of RNA-seq ( Wu et al, 2019 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional enrichment analysis showed that DEGs between the Control and WFS groups were associated with 34 KEGG pathways, including starch and sucrose metabolism, metabolic pathways, retinol metabolism, glycolysis-gluconeogenesis and lysosome ( Figure 5), which were reported to be linked to pathogen interaction (Wu et al, 2019).…”
Section: Transcriptome Difference Between Control and Wfsmentioning
confidence: 99%